1994
DOI: 10.1002/tcm.1770140405
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA adduct levels in human placenta from polychlorinated biphenyl exposed women and smokers in which CYP 1A1 levels are similarly elevated

Abstract: Previous studies demonstrated that cigarette smoking is associated with high elevations in levels of both cytochrome P450 1A1 (CYP1A1) and DNA adducts in human placenta. To date, the identity of the smoking related DNA adducts is not known. The DNA adducts identified in placenta of smokers could result from chemicals present in cigarette smoke, substances formed by CYP 1A1 metabolic activation of endogenous compounds, noncigarette related exposures or a combination of these processes. Exposure to contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Consistent with our findings, previous studies of adult populations have seen significant associations between active smoking and WBC PAH-DNA adduct levels (16,49,50), although results have not been consistent (51). Several prior studies using the 32P-postlabeling method, which measures a broad spectrum of adducts bound to DNA, have seen an association between maternal smoking and adduct levels in fetal samples (52)(53)(54). However, studies using methodologies specific to PAH-DNA adducts have not (52,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, previous studies of adult populations have seen significant associations between active smoking and WBC PAH-DNA adduct levels (16,49,50), although results have not been consistent (51). Several prior studies using the 32P-postlabeling method, which measures a broad spectrum of adducts bound to DNA, have seen an association between maternal smoking and adduct levels in fetal samples (52)(53)(54). However, studies using methodologies specific to PAH-DNA adducts have not (52,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers of human exposure, dose, and genetic effects in the general population have recently been studied with respect to exposures from environmental pollution (5)(6)(7)11,13,(28)(29)(30)(31)(32). Perera et al (5) found that the exposure to environmental pollution in the Silesian region of Poland was associated with a significant increase of DNA adducts, SCE, and CA, as well as with a frequency of ras oncogene overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus Gallagher and coworkers did not see elevated DNA adduct levels in the placentas of non-smoking Taiwanese women who had been exposed to PCBs and polychlorinated dibenzofurans compared to non (less)-exposed non-smoking women from Taiwan or the USA [27]. They also measured arylhydrocarbon hydroxylase (AHH) activity in these tissues and found similar levels in placentas from American smokers and Taiwanese PCB-exposed non-smokers, but higher DNA adduct levels only in the American smoker samples, indicating that AHH induction alone is not sufficient to increase DNA adduct levels.…”
Section: Relevance – Evidence For Dna Damage By Pcbs In Nature Andmentioning
confidence: 99%